Hubungan Dukungan Sosial dengan Masalah Psikososial pada Remaja Awal (12-14 Tahun) di Pesantren - Kosika, Denny; Yuniar Sari, Niken; Kurniawan, Didi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background: Early adolescence is the gateway to psychosocial problems. Adolescence is a transitional period of change both physically and psychologically. Psychosocial problems that occur in adolescents can cause low self-esteem, impaired self-image, and depression. This study aims to determine the relationship between social support and psychosocial problems in early adolescents at the Pekanbaru City Islamic Boarding School. Methods: This study used a correlation descriptive design and a cross sectional approach. The instruments used in this study were the Child and Adolescent Social Support Scale (CASSS), and the Pediatric Symptom Checklist-Youth Report (PSC-Y35). The research sample consisted of 194 respondents who were taken based on inclusion criteria using a simple random sampling technique. The analysis used was bivariate analysis using the chi square test and simple logistic regression analysis. Result: There are 19.1% of adolescents who have high category social support, as many as 27% of adolescents experience psychosocial problems. The results of statistical tests showed that there was a significant relationship between social support and psychosocial problems in early adolescents at Islamic boarding schools with a p value (0.007) <alpha (0.05). Conclusion: Social support has a significant relationship with psychosocial problems in adolescents in Islamic boarding schools.